2007
DOI: 10.1128/mcb.00659-06
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the ETS Factor Gabpα Disrupts Neuromuscular Junction Synaptic Function

Abstract: The GA-binding protein (GABP) transcription factor has been shown in vitro to regulate the expression of the neuromuscular proteins utrophin, acetylcholine esterase, and acetylcholine receptor subunits ␦ and through the N-box promoter motif (5-CCGGAA-3), but its in vivo function remains unknown. A single point mutation within the N-box of the gene encoding the acetylcholine receptor subunit has been identified in several patients suffering from postsynaptic congenital myasthenic syndrome, implicating the GA-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…A caveat noted by Dong et al was that gene targeting did not completely eliminate Shp2 expression in muscles. Indeed it can be difficult to be sure of complete inactivation of any gene in multinucleated muscle fibres (Jaworski et al, 2007;O'Leary et al, 2007). Expression of the Cre recombinase gene was often insufficient to completely excise loxP-targeted genes, such as Shp2, ErbB2 and ErbB4 in multinucleated muscle cells (Dong et al, 2006;Escher et al, 2005;Jaworski and Burden, 2006;Leu et al, 2003), and studies that target the inactivation of genes in specific cells types (such as motor nerve and muscle) do not address acute action and/or actions of neuregulin-1 at later stages of NMJ development.…”
Section: Discussionmentioning
confidence: 99%
“…A caveat noted by Dong et al was that gene targeting did not completely eliminate Shp2 expression in muscles. Indeed it can be difficult to be sure of complete inactivation of any gene in multinucleated muscle fibres (Jaworski et al, 2007;O'Leary et al, 2007). Expression of the Cre recombinase gene was often insufficient to completely excise loxP-targeted genes, such as Shp2, ErbB2 and ErbB4 in multinucleated muscle cells (Dong et al, 2006;Escher et al, 2005;Jaworski and Burden, 2006;Leu et al, 2003), and studies that target the inactivation of genes in specific cells types (such as motor nerve and muscle) do not address acute action and/or actions of neuregulin-1 at later stages of NMJ development.…”
Section: Discussionmentioning
confidence: 99%
“…The GABP␣/␤ complex has been shown to have versatile roles in regulating basic cellular functions and tissue-specific functions (9,26,31). Gene-targeting studies of the DNA binding GABP␣ subunit have revealed its critical roles during embryogenesis (25), during the reentry of the cell cycle (41), and in synaptic function at the neuromuscular junction (22,24). In the immune system, we and others showed that GABP critically regulates IL-7R␣ expression (5,38).…”
Section: Vol 28 2008 Gabp␤1l Is Dispensable For Lymphocyte Developmmentioning
confidence: 99%
“…Recent studies revealed that GABP␣ can recruit the histone acetyltransferase p300 to the acetylcholine receptor ε subunit promoter for its activation in subsynaptic nuclei (24). However, contradictory results on the effect of disrupting Gabpa alleles on the formation and function of neuromuscular junction were recently reported (16,22). In the immune system, GABP has been reported to increase transcription from the interleukin-2 (IL-2) enhancer (1) and the Fas promoter (19) in T cells.…”
mentioning
confidence: 99%
“…7 Genetic inactivation of individual Ets factors in the mouse has revealed unique, essential Ets functions in diverse biological processes, including hematopoiesis, immune function, lymph/angiogenesis, neurogenesis/neuromuscular function, spermatogenesis, early embryonic patterning, and development of extraembryonic tissues. 1,[7][8][9][10][11][12][13][14][15][16] Interestingly, such studies have been remarkable for the absence of phenotypes in a number of tissues with Ets expression, especially those comprising solid organs. The relative paucity of Ets phenotypes in such tissues appears to be attributable to the multiplicity of expression of different Ets factors in the same cell, combined with the ability of co-expressed Ets factors to compensate for each other's function.…”
mentioning
confidence: 99%